Fight or flight: reimagining Charles Jesse “Buffalo” Jones' conservation efforts through a bison's embodied perspective - Wilson, Michelle (Frontiers in Human Dynamics, 2024)
In this speculative historical essay, I employ Buffalo Jones’ records to expand upon who can have a voice in the archive, thereby undermining the anthropocentrism inherent in the chronicling of bison conservation. Indeed, this work of ‘fictocriticism’ deploys empathy to recenter the more-than-human voice and ironically uses the observations of the bison’s tormentor to move beyond a simplistic anthropomorphic representation. The essay briefly introduces Jones and his contentious legacy as a murderer of Indigenous peoples, buffalo hunter and, later, a central figure in early bison conservation. The essay then shifts into a first-person account of the pursuit and capture of the last remaining southern plains bison from the Texas Panhandle from a cow’s embodied perspective. The bison’s first-person perspective as one of Jones’ prey brings an immediacy to a history that has often been retold to centre man’s mastery and supremacy. Finally, this essay employs footnotes as a critical intervention by connecting the speculative narrative to Jones’ written accounts in published journals. These two narrative approaches demonstrate the significance of bison kinship and how anthropocentrism and white supremacy’s entangled ideologies blinded Jones to the worthiness of these others’ lifeways. The written submission is accompanied by two audio artworks based on this essay. In creating affective, sound-designed audio works, I have intentionally extracted the archival-research-based narrative from a white supremacist, a patriarchal written tradition for critical purposes.